1994
DOI: 10.5194/npg-1-64-1994
|View full text |Cite
|
Sign up to set email alerts
|

Surface flow structure of the Gulf Stream from composite imagery and satellite-tracked drifters

Abstract: Abstract. A unique set of coutemporaneous satellite-tracked drifters and five-day composite Advanced Very High Resolution Radionmeter (AVHRR) satellite imagery of the North Atlantic has been analyzed to examine the surface flow structure of the Gulf Stream. The study region was divided into two sections, greater than 37° N and less than 37° N, in order to answer the question of geographic variability. Fractal and spectral analyses methods were applied to the data. Fractal analysis of the Lagrangian trajectorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Fractal scaling of meandering river planforms (and ocean currents) was originally suggested by Mandelbrot (1983, p. 99, 111), and analyzed by Snow (1989), Nikora (1991), Mullen and Kirwan (1994), and Montgomery (1996). For about 50 meandering rivers, Snow (1989) and Montgomery (1996) found that the meanders themselves scale over one order of magnitude.…”
Section: River Scaling Statisticsmentioning
confidence: 98%
“…Fractal scaling of meandering river planforms (and ocean currents) was originally suggested by Mandelbrot (1983, p. 99, 111), and analyzed by Snow (1989), Nikora (1991), Mullen and Kirwan (1994), and Montgomery (1996). For about 50 meandering rivers, Snow (1989) and Montgomery (1996) found that the meanders themselves scale over one order of magnitude.…”
Section: River Scaling Statisticsmentioning
confidence: 98%